2017
DOI: 10.1002/admi.201700640
|View full text |Cite
|
Sign up to set email alerts
|

Monodispersed, Highly Interactive Facet (111)‐Oriented Pd Nanograins by ALD onto Free‐Standing and Flexible Electrospun Polymeric Nanofibrous Webs for Catalytic Application

Abstract: An atomic layer deposition (ALD) of monodispersed palladium (Pd) nanograins (≈2 nm) onto electrospun polymeric nanofibers (NF) is presented. By ALD, monodispersed Pd nanograins with (111) exposed facets are decorated on the surface of the free‐standing flexible nanofibrous webs (NW). The Pd nanograin‐decorated free‐standing NW exhibit catalytic reduction of 4‐nitrophenol to 4‐aminophenol. Even under low loading capacity (≈20 µg mg−1), Pd nanograins manifest effective catalytic performance which can be referred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…[30] It has been reported as av ersatile techniquef or the functionalization of electrospun fibers with numerous metal oxides such as Pt, [31] Pd, [32] Zn, [33] and Ru. [24] In addition, controlling the facets [34] ando perating at al ower temperature than ac onventional chemical vapor deposition technique widensi ts application for numerous nanoparticles and thin-film deposition. Therefore, the ALD methodw as chosen to prepareauniform thin coating of Ni oxyhydroxy catalysts on PIM-CF.…”
Section: Introductionmentioning
confidence: 99%
“…[30] It has been reported as av ersatile techniquef or the functionalization of electrospun fibers with numerous metal oxides such as Pt, [31] Pd, [32] Zn, [33] and Ru. [24] In addition, controlling the facets [34] ando perating at al ower temperature than ac onventional chemical vapor deposition technique widensi ts application for numerous nanoparticles and thin-film deposition. Therefore, the ALD methodw as chosen to prepareauniform thin coating of Ni oxyhydroxy catalysts on PIM-CF.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, numerous studies on Pd-NP functional nanofiber systems have been reported for different catalytic reactions, including the photocatalysis of methylene blue, 32 Heck coupling reactions between iodobenzene and acrylates, 33 and hydrogenation of aldehydes 34 and p-nitrophenol. 35 p-Nitrophenol is a nitroarene-type of molecule and can be found in wastewater, 36 and can damage the central nervous system, liver and kidneys. 37 It is thus considered as a pollutant by the U.S. Environmental Protection Agency (EPA).…”
Section: Resultsmentioning
confidence: 99%
“…11 In addition to these approaches, atomic layer deposition (ALD) of metals or metal oxides onto electrospun nanowebs has emerged as a more advantageous technique since it promotes the growth of nanoparticles in an atomically controlled manner by chemical attachment to surface oxygen atoms and therefore, allows producing nanoparticles or ultrathin nanolayers on the supporting materials. [12][13][14][15][16][17][18] As the entire process follows a layer-bylayer growth, the deposition of atoms gives rise to nanostructures with atomically controlled interfaces. Furthermore, ALD as a chemical vapor deposition technique enables the chemical attachment of atoms and their subsequent growth into nanoparticles or nanolayers so that the materials can be reused many times without the loss or with a minimal loss of catalytic nanomaterials from the material's surface.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, our research group has made a signicant contribution in this area by exploiting different combinations of electrospun nanobrous materials as substrates and ALD of metal oxides and metals for catalytic purposes. [12][13][14][15][16]19 The ALD technique is based on self-terminating gas-solid reactions 20 and is mainly composed of repetitive cycles of the following reactions: (i) the reaction of a metal-ligand (ML) molecule and (ii) the reaction of water. 21 The rst step is likely to happen through ligand (L) swap with one or more surface OH groups, releasing a gaseous product, HL, while attaching the metal-ligand (ML) species to the surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation